Numerical Simulation of Inline Forces on a Bottom-Mounted Circular Cylinder Under the Action of a Specific Freak Wave - Wang, Yuqi; Xu, Fuyou; Zhang, Zhanbiao (Frontiers in Marine Science, 2020)
Freak waves pose a great threat to the tension-leg platforms (TLPs) and monopile foundations of offshore wind turbines (OWTs), which necessitates comprehensive investigations on the characteristics of freak waves and the wave actions on those offshore renewable energy structures with circular cylinder. The recorded freak wave series 'New Year Wave' (NYW) was numerically simulated using the Computational Fluid Dynamics method. The compensation measure was adopted to effectively improve simulation accuracy. Under the action of the NYW, the inline forces and secondary load cycle on a vertical-mounted cylinder, as the classic form for the TLPs and foundation of OWTs, were fully addressed. The simulation results were compared with the empirical formulations and experimental data to reveal the differences and the possible causes. The development of secondary load cycle was found to be closely related to the downstream vortex and return flow, which induces the reduction of the wall pressure and thus the inline force. The maximum inline forces vary with the cylinder position relative to the wave peak, and the simulation results reveal that the linear inline forces calculated by Morison formulation may be less than 65% of the total wave forces.